2008
DOI: 10.1007/s00296-008-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knee proprioception and effects of proprioception exercise in patients with benign joint hypermobility syndrome

Abstract: The first aim is to show if there is a disorder in proprioception in cases with benign joint hypermobility syndrome (BJHS) when compared to healthy subjects. The second aim is to evaluate the effect of proprioception exercise in BJHS cases. To evaluate the proprioceptive sensibility of the knee joint with 40 BJHS and 30 healthy subjects enrolled in the study. Then, cases with BJHS were randomized into two groups; proprioceptive exercises were applied to 15 patients for 8 weeks in clinic and 25 patients were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
140
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 20 publications
3
140
0
2
Order By: Relevance
“…[9][10][11][12] Hypermobility syndrome is a systemic disorder which affects virtually all joints, and the lack of proprioception is a wellknown feature. [6,7] Impaired joint proprioception can lead to poor postural control and balance in patients with HMS, as has been previously demonstrated by the research. [13,26] However, a review of the literature did not reveal any studies which have evaluated balance problems in FMS patients and their association with hypermobility.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…[9][10][11][12] Hypermobility syndrome is a systemic disorder which affects virtually all joints, and the lack of proprioception is a wellknown feature. [6,7] Impaired joint proprioception can lead to poor postural control and balance in patients with HMS, as has been previously demonstrated by the research. [13,26] However, a review of the literature did not reveal any studies which have evaluated balance problems in FMS patients and their association with hypermobility.…”
Section: Discussionmentioning
confidence: 63%
“…[5] Balance control is a highly specific proprioception in the performance of daily activities and is essential in all postures and situations, both static (maintaining an upright posture) and dynamic (in locomotion). [5] A lack of proprioception seems to be a prominent feature in HMS, [6,7] and reduced balance has been described for subjects with this disorder. [8] The coexistence of HMS and FMS has been shown in previous studies in which it was suggested that hypermobility may play a prominent role in the pathogenesis of pain in women with FMS.…”
Section: Discussionmentioning
confidence: 99%
“…en, the subject was instructed to reposition the segment at the same angle in which it was held for 10 seconds, stopping the dynamometer manually by pressing the stop button. e same procedure was repeated for the 20º of inversion position [39][40][41][42] . e di erence between the position establish by the protocol and the one assumed by the subject was considered as the proprioceptive de cit (absolute angular error -AAE, in degrees).…”
Section: Discussionmentioning
confidence: 99%
“…24 Research on the conservative treatment of BJHS is quite limited, with most high-level studies (randomized controlled trials) focused on knee pain and lowlevel studies (single-group prospective cohort, case series, case reports) focused on the spine or full body pain. [25][26][27][28][29][30][31][32][33] Proprioceptive or balance exercises have been the most widely studied treatment approach, showing some promise for knee pain. [25][26][27] As a result of the limited amount of high-level studies, standardized treatment guidelines are not available, with treatment recommendations based on low levels of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33] Proprioceptive or balance exercises have been the most widely studied treatment approach, showing some promise for knee pain. [25][26][27] As a result of the limited amount of high-level studies, standardized treatment guidelines are not available, with treatment recommendations based on low levels of evidence. 34 It is generally recommended that, for patients with BJHS and chronic pain, a multidisciplinary approach consisting of physiotherapy (strengthening and proprioceptive exercises), cognitive behavioral therapy, and pharmacology is best.…”
Section: Introductionmentioning
confidence: 99%